Dynamic multilateral markets - Arnold Polanski; Emiliya A. Lazarova (Fondazione Eni Enrico Mattei (FEEM), 2011)
We study dynamic multilateral markets, in which players' payoffs result from coalitional bargaining. In this setting, we establish payoff uniqueness of the stationary equilibria when players exhibit some degree of impatience. We focus on market games with different player types, and derive under mild conditions an explicit formula for each type's equilibrium payoff as market frictions vanish. The limit payoff of a type depends in an intuitive way on the supply and the demand for this type in the market, adjusted by the type-specific bargaining power. Our framework may be viewed as an alternative to the Walrasian price-setting mechanism. When we apply this methodology to the analysis of labor markets, we can determine endogenously the equilibrium firm size and remuneration scheme. We find that each worker type in a stationary market equilibrium is rewarded her marginal product, i.e. we obtain a strategic underpinning of the neoclassical wage. Interestingly, we can also replicate some standardized facts from the search-theoretical literature such as positive equilibrium unemployment.
Keywords: C71; C72; C78; J30; L20; 330; Multilateral Bargaining; Dynamic Markets; Labor Markets